METHODOLOGICAL APPROACHES TO DEVELOPING MECHANISMS FOR INNOVATIVE DEVELOPMENT OF MARKETING SYSTEMS IN PHARMACEUTICAL ENTERPRISES - POKOTYLOVA, Valentyna; PASHKOVA, Alla; SHAPOVALOVA, Valentyna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article reveals methodological approaches to the formation of mechanisms for the innovative development of marketing systems in pharmaceutical enterprises. It is established that the innovative orientation of pharmaceutical marketing is driven by the high dynamics of scientific and technological progress, the evolution of the regulatory framework, and changes in consumer behavior models. It is found that marketing activities in the pharmaceutical sector should be integrated into the overall innovation development system with a focus on product, technological, and service innovations. The role of flexible manufacturing technologies in ensuring product individualization according to the target audience’s needs is emphasized. It is stated that the transformation of sales policy is due to the spread of digital technologies, which contribute to logistics optimization and strengthening interaction with end consumers. The prospect of creating integrated digital platforms that combine online ordering, telemedicine, and logistics support functions is outlined. The relevance of a personalized approach in enterprise communication policy aimed at individualized informational support is noted. The growing role of digital communication channels, content marketing, mobile applications, and social networks in building effective communications is explained. The necessity of forming a comprehensive system of innovative communications ensuring synergy of knowledge, trust, and commercial efficiency among manufacturers, medical professionals, and consumers is substantiated. It is emphasized that the marketing subsystem of the innovation development mechanism includes analytical, strategic, and tactical tools. The need to integrate marketing analytics with big data technologies, artificial intelligence, and predictive modeling is outlined. The importance of developing a system of marketing efficiency criteria considering market dynamics, digital transformation, and customer loyalty level is stated. It is determined that competitive advantages can be achieved through the use of personalized strategies, AI analytics, and educational platforms for consumers and medical professionals. Examples of such tools are given, including Doktor.se, MyHealthTeams, Pfizer, and Johnson & Johnson initiatives. The importance of ethical marketing standards as a factor in maintaining brand trust is noted. The need for a balance between innovation, efficiency, and social responsibility in the context of post-pandemic market transformation is emphasized.